2009
DOI: 10.4049/jimmunol.0804165
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 Suppresses Calcium-Mediated Costimulation of Receptor Activator NF-κB Signaling during Human Osteoclast Differentiation by Inhibiting TREM-2 Expression

Abstract: Induction of effective osteoclastogenesis by RANK (receptor activator of NF-κB) requires costimulation by ITAM-coupled receptors. In humans, the TREM-2 (triggering receptor expressed on myeloid cells 2) ITAM-coupled receptor plays a key role in bone remodeling, as patients with TREM-2 mutations exhibit defective osteoclastogenesis and bone lesions. We have identified a new rapidly induced costimulatory pathway for RANK signaling that is dependent on TREM-2 and mediated by calcium signaling. TREM-2-dependent ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 59 publications
6
72
0
1
Order By: Relevance
“…In the present study, we observed a down-regulation of trem2 expression in response to LPS-PG alone. RANKL itself also suppresses trem2 expression, as shown in the present study and by others (70). Therefore, although RANKL plus LPS-PG down-regulate trem2 expression, it is unlikely that LPS-PG inhibits RANKL-induced osteoclastogenesis by down-regulation of trem2.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, we observed a down-regulation of trem2 expression in response to LPS-PG alone. RANKL itself also suppresses trem2 expression, as shown in the present study and by others (70). Therefore, although RANKL plus LPS-PG down-regulate trem2 expression, it is unlikely that LPS-PG inhibits RANKL-induced osteoclastogenesis by down-regulation of trem2.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, addition of LPS-PG results in a diminished expression of RANKL-induced oscar mRNA, whereas IL-1 increases RANKL-induced oscar expression, indicating a possible role of OSCAR in the differential regulation of RANKL-induced osteoclastogenesis by TLR2 and IL-1R signaling. Therefore, based on our finding and previous reports (70), it is likely that the relative importance of individual costimulatory receptors varies with time, expression of ligands, and physiological context. Thus, TREM2 plays a dominant costimulatory role early in human osteoclast differentiation, at the stage of generating osteoclast precursors.…”
Section: Discussionsupporting
confidence: 76%
“…-/-mice were comparable to those in control mice ( Figure 1C and Table 1 (9,(12)(13)(14)(15)(16)(17). Activation of PLCγ2 and downstream calcium-signaling pathways plays an essential role in NFATc1 induction during osteoclastogenesis (16,18,19).…”
Section: Dap12mentioning
confidence: 61%
“…RANK signaling induces a transient increase in PLCγ2 activity, but does not regulate its expression and is not required for basal PLCγ2 activity in osteoclast precursors. Instead, basal PLCγ2 activity, which has been observed in myeloid cells including osteoclast precursors (17,(21)(22)(23)(24), appears to be maintained by tonic ITAM signaling mediated by engagement of ITAM-associated receptors by constitutively expressed ligands (13); consistently, addition of ligands/agonists for ITAMassociated receptors is not required for osteoclast differentiation in vitro. Importantly this basal level of costimulation and PLCγ2 activation together with RANKL is sufficient for NFATc1 induction and osteoclast differentiation (16,18,19).…”
Section: Fcrgmentioning
confidence: 95%
“…Downregulation of TREM-2 expression resulted in diminished RANKL-induced activation of the CaMK-MEK-ERK pathway and decreased the expression levels of NFATc1, the master regulator of osteoclastogenesis. 31 Fox et al demonstrated that TGF-b primed monocytes for osteoclast formation within 24 h by directly inducing cytoplasmic NFATc1 expression, although TGF-b was unable to stimulate NFATc1 nuclear translocation. TGF-b enables NFATc1 expression during osteoclastogenesis.…”
Section: Modulation Of Treg Cells On Osteoclast Functionsmentioning
confidence: 99%